Manejo de las podas en el cultivo de Cacao (Theobroma cacao L.), en la parroquia Pimocha - Cotto Galarza, Josué Daniel (2019)
Cocoa is a tropical crop that has its origin in the humid Amazon rainforest, at the headwaters of the Amazon River, where Ecuador, Colombia and Peru border today. The commercial cultivation of cocoa in Ecuador begins in the mid-16th century and by 1593 there were Spanish colonial registers on the areas planted on the banks of the Guayas River and cocoa exports to Spain. In recent years, in the provinces of Orellana and Sucumbíos, the area planted has increased by at least 14,000 ha of cocoa, 75% of which corresponds to the National type. Therefore, it is essential to develop the cultural work correctly, including pruning, during the different stages of the crop and under certain cycles. Pruning is considered as a practice of cutting or eliminating all unnecessary pacifiers and branches which runs after eight months. This allows to stimulate the development of the branches and maintain an adequate bearing of the tree. In the Pimocha parish there are the necessary inputs and tools to develop each of the tasks, especially pruning that are very important both in the physiological and phytopathological part of the cocoa crop. In the Pimocha area, Mr. Felipe Zuñiga mentions that he has approximately 1.5 hectares dedicated to the production of cocoa, whose area is planted by the CCN 51 cocoa variety, even distancing from 2.50 m x 2.50 m to 3.00 m x 3.00 m. In turn I do not mention that it is necessary to perform the types of pruning that corresponds to the time and age of the crop to favor the production, development and growth of the cocoa crop. Pruning seeks to eliminate imperfect branches that are in poor condition, diseased ears and dead parts of the plant. This positively and negatively influences performance for months and even years. By pruning you can design the shape and distribution of the cocoa tree. It has been proven that insect pests and diseases are much more propagative in cocoa trees without pruning